1987
DOI: 10.2170/jjphysiol.37.955
|View full text |Cite
|
Sign up to set email alerts
|

Roles of .GAMMA.-aminobutyric acid and serotonin in the arcuate nucleus in the control of prolactin and luteinizing hormone secretion.

Abstract: Summary The effects of implantation of y-aminobutyric acid (GABA) and serotonin (5-HT) into the arcuate nucleus (ARC) on serum luteinizing hormone (LH) and prolactin (PRL) were examined in the conscious ovariectomized rat. Following implantation of 5-HT, but not GABA, serum PRL was significantly increased. While 5-HT did not affect pulsatile LH secretion, GABA significantly decreased the mean LH concentration and pulse frequency, but not amplitude.Key words : arcuate nucleus, y-aminobutyric acid, serotonin.Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
2
8
1
Order By: Relevance
“…Since LH pulses occurred in association with MUA volleys, the result was in con sonance with previous ones showing decreases in the mean LH level and the pulse frequency after administra tion of GABA or muscimol into the brain [9, 11,12,14] and i.v. injection of AOAA [13] in ovariectomized rats.…”
Section: Discussionsupporting
confidence: 89%
“…Since LH pulses occurred in association with MUA volleys, the result was in con sonance with previous ones showing decreases in the mean LH level and the pulse frequency after administra tion of GABA or muscimol into the brain [9, 11,12,14] and i.v. injection of AOAA [13] in ovariectomized rats.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that the GABAergic inhibition of pul satile LH secretion [1,2] is partially mediated by GABAb receptors, in addition to a mediation by classic GABAa receptors [4,5], although the relative contribution of these receptors is unknown at present. The GABAb re ceptor-mediated suppression of the LH pulse frequency may have a causal relationship to the baclofen-induced inhibition of the preovulatory LH surge [8,10], as dis cussed elsewhere [8].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that y-aminobutyric acid (GABA), a major inhibitory neurotransmitter in the central nervous system, is involved in the neuroendocrine control of the episodic LH secretion. The existing pulsatile LH secre tion is inhibited by reducing the degradation of the en dogenous GABA [1] or by centrally applying GABA in ovariectomized rats [2]. LH pulses are preceded by a significant reduction of preoptic/anterior hypothalamic GABA release [3], Receptors mediating the GABAergic transmission have been classified into two major subtypes, GABAa and GABAb, according to their pharmacological proper ties.…”
mentioning
confidence: 99%
“…This amino acid also affects several as pects of neuroendocrine function by actions in the brain, in cluding in the ARC [22]. In fact, implantation of GABA directly into the ARC has been reported to decrease the release of lu teinizing hormone [23]. Again, extracellular recordings have in dicated that GABA decreases the activity of most ARC neurons [24], GABA acts on at least two different receptors.…”
mentioning
confidence: 99%